Mementoes: Raul Seixas’ fans and their collections - Abonizio, Juliana (2015)
Raul Seixas’ fans are collectors of several objects. In order to unveil the relationship of the collectors with the idol, with others, and with themselves, I reviewed the letters sent to Raul Rock Club and analyzed his collection. The articulations among the various forms of relating with objects of the singer, or that refer to him, show that the collectible objects, more than vehicles of social reproduction, can function as poetic devices.